DESCRIPTION OF LEUKOSIT Pangasius hypophthalmus THAT IS INFECTED BY Aeromonas hydrophila AND TREATED WITH SOLUTION OF Mangifera indica L. - Dea Switzelin H; Iesje Lukistyowati; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRAKThis research was conducted from October to December 2018 at the Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine, University of Riau. This study aims to obtain the best dose from the solution of harumanis mango seeds (Mangifera indica L.) to treat catfish (P. hypophthalmus) infected with A. hydrophila seen from the picture of leukocytes. While the expected benefits are a solution of harumanis mango seeds can be used as a medicine to treat Motile Aeromonas Septicemia (MAS) disease. The method used in the research is the experimental method using a completely randomized design (CRD) with five levels of treatment, namely (Kn): Infected fish A. hydrophila and untreated mango seed solution, (Kp): Fish infected A. hydrophila are not treated with mango seed solution, (P1): Fish infected A. hydrophila were soaked with mango seed solution at a dose of 1600 ppm, (P2): Fish infected A. hydrophila were immersed in a manga seed solution at a dose of 1800 ppm (P3): Infected fish A. hydrophila is soaked in a solution of mango seeds at a dose of 2000 ppm. The leukocyte parameters measured were total leukocytes, leukocrit percentage, leukocyte differentiation and phagocytic activity.The results showed that the solution of harumanis mango seeds was influential in treating catfish infected with A. hydrophila, the dose of 2000 ppm mango seed solution was the best dose in the treatment of catfish infected with A. hydrophila seen from a total leukocyte of 7.37 x 104 cells / mm3, leukocrit levels of 2%, phagocytic index of 35.67%, and survival rate reached 80%. While the percentage of 81% lymphocytes, 10.67% monocytes and 8.33% neutrophils. The results of measurements of water quality during the study, namely temperature 28.2-28.50C, pH 5-6.7 dissolved oxygen 5-6.7 mg / L, and ammonia 0.02 mg / L. Keywords: Description of Leukosit, Pangasius hypophtalmus, Mangifera indica L., Aeromonas hydrophila